ANALYSIS OF THE APPARATUS QUALITY IN KULANGO SUB-DISTRICT OFFICE OF BUOL REGENCY - Armin, Sri Yanti UM; Aneta, Yanti (Public Policy Journal, 2022)
The low quality of human resources, especially apparatus at the Kulango Sub-District Office, Biau District, Buol Regency, affects the quality of their works due to the lack of mastery of the field that is currently being worked on. This study to explore the apparatus quality at the Kulango Sub-District, Biau District, Buol Regency. This descriptive study employed a survey approach. Conducted from August to September 2019, this study involved 24 apparatus and officers at the Kulango Sub-District Office, Biau District, Buol Regency. The data collected were primary data and secondary data. Primary data were obtained through interviews, observation, and documentation. The data obtained were processed using frequency table data analysis techniques. The results showed that the quality of the apparatus resources at the Kulango Sub-District Office, Biau District, Buol Regency was good based on the indicators of knowledge, skills, abilities, and experience. However, the strategic plan and understanding of job descriptions for the apparatus of the office must be improved. Although other indicators already had good results, improvements need to be made to produce quality apparatus resources.